Experimenting with the internet, A guide for chemistry students / Thomas Gardner - Gardner, Tomas (1996)
welcome to the net, what is the internet, why do we have an internet, spreading the net, know your hosts, the seven faces of the internet, remote log,(telnet), file transfer protocol FTP, electronic mail E Mai, Usenet news, gopher, hypertext documents HTTP, custom applications, finding needles in haystacks, references; tools of the trade, hooking into the net, the computer, the connection, the service provider, the joy of text, SLIP emulators, TCP/IP and client software, the TCP stack, client software, the web browser, protocols, other client software, where to obtain software, helpers and plug, ins, other programs, references; surfing for chemists, how might a chemistry student use the internet; chem central, references glossary.